Experimental determination and analysis of the transverse pressure difference in a wire-wrapped rod bundle. (May 2021) - Childs, Mason; Vaghetto, Rodolfo; Jones, Philip; Goth, Nolan; Hassan, Yassin
Highlights: Transverse pressure difference in a wire wrapped hexagonal bundle was investigated. Maximum pressure was found at wall 90 ∘ before the leading edge of the wire. Minimum pressure was observed 90 ∘ away from the lagging edge of the wire. Pressure variation was characterized as function of the wire position and flow regime. Abstract: Wire-wrapped rod bundles are widely used in different applications for their enhanced heat transfer capability. The complex behavior of the flow in these rod bundles is strongly affected by the geometrical parameters, and flow regime. Experimental measurements of the transverse pressure difference (between adjacent faces) of a replica of a 61-rod wire-wrapped hexagonal bundle have been conducted under a wide range of Reynolds number (3, 000–18, 000), to study the effects of the wire azimuthal position for transition and turbulent flow regimes. As a result of the higher horizontal velocity, the transverse pressure difference was found to increase with the bundle Reynolds number. At higher Reynolds number, the maximum (positive) transverse pressure difference between two adjacent faces occurred when the wire is directed at the corner between these faces ( θ = 0 ∘ ), with the minimum (negative) occurring at a wire azimuthal location of θ = 120 ∘ . Pressure at adjacent walls equalizes at an angle 60 ∘ < θ < 120 ∘, and near θ = − 90 ∘ . For the lower Reynolds numbers investigated, a positive minimum pressure difference was observed at θ = 0 ∘ . The experimental results improved the understanding of the flow behavior in wire-wrapped bundles, and provided a unique set of data that can be used for validation of high-fidelity computational fluid dynamics codes.